Engineered small metal‐binding protein tag improves the production of recombinant human growth hormone in the periplasm of Escherichia coli - Pérez Pérez, David Antonio; Pioquinto Avila, Elizeth; Arredondo Espinoza, Eder Ubaldo; Morones Ramírez, José Rubén; Balderas Rentería, Isaías; Zárate Kalfópulos, Xristo (2020)
Fusion proteins play an important role in the production of recombinant proteins in Escherichia coli. They are mostly used for cytoplasmic expression since they can be designed to increase the solubility of the target protein, which then can be easily purified via affinity chromatography. In contrast, fusion proteins are not usually included in construct designs for periplasmic production. Instead, a signal sequence is inserted for protein transport into the periplasm and a C-terminal his-tag added for subsequent purification. Our research group has proposed the small metal-binding protein (SmbP) isolated from the periplasm of Nitrosomonas europaea as a new fusion protein to express recombinant proteins in the cytoplasm or periplasm of E. coli. SmbP also allows purification via immobilized metal affinity chromatography using Ni(II) ions. Recently, we have optimized the periplasmic production of proteins tagged with SmbP by exchanging its native signal peptide with one taken from pectate lyase B (PelB), substantially increasing the amount of protein produced. In this work, we have expressed and purified soluble bioactive human growth hormone (hGH) tagged with PelB-SmbP and obtained the highest periplasmic production reported for this protein so far. Its activity, tested on Nb2-11 cells, was equivalent to commercial growth hormone at 50 ngmL 1. Therefore, we strongly recommend the use of PelBSmbP as a protein tag for the expression and purification of hGH or other possible target proteins in the periplasm of E. coli.